Feasibility, Acceptability, and Preliminary Efficacy of Dignity Therapy in Patients With Early Stage Dementia and Their Family. A Pilot Randomized Controlled Trial - Jenewein, Josef; Moergeli, Hanspeter; Meyer-Heim, Tatjana; Muijres, Peter; Bopp-Kistler, Irene; Chochinov, Harvey M.; Peng-Keller, Simon (Frontiers in Psychiatry, 2021)
Purpose: Dementia is the major cause for disability and dependence in older people and associated with considerable psychological burden. The aim of this study was to determine the feasibility, acceptability and preliminary efficacy of Dignity Therapy, a brief psychotherapeutic intervention to enhance dignity and reduce psychological burden, in patients with early stage dementia and in their families. Materials and Methods: In this randomized, waitinglist-controlled clinical trial a total of 54 patients with new diagnosis of early stage dementia and 54 family members were randomly assigned to immediate treatment (n=28) or delayed treatment (n=26) after 3 months waiting. The main outcomes were feasibility: proportion of screened and invited patients who consented participation; Acceptability: number of drop-outs, and satisfaction with treatment; Efficacy: psychological burden (Hospital Anxiety and Depression Scale - HADS), quality of life (WHOQOL-Bref), and sense of dignity (Patient Dignity Inventory - PDI). Results: In total 38.6% (CI95%: 30.7 % to 47.1 %) of all eligible patients consented and were enrolled. Along the study six participants (11.1%; CI95%: 3.7 % to 20.4 %) dropped out. Patients’ satisfaction with the treatment was high and with no significant difference between the groups. HADS scores were significantly lower in both groups at the 3-months follow-up. There was no significant group by time interaction effect (F=0.71; df=2, 70.3; P=0.50). PDI scores decreased significantly (i.e., improvement of dignity) in the immediate group, but the group by time interaction effect was not statistically significant (F=2.29; df=1, 46.8; P=0.14). After pooling patients’ data of both groups, Dignity Therapy resulted in significant improvements in almost all outcome measures. Patients’ family members reported high satisfaction with the intervention. Conclusions: Our findings suggest that Dignity Therapy is feasible and highly accepted in patients with early stage dementia. Patients reported significant improvements, however, there was no significant effect of the intervention in the immediate treatment group compared to the delayed group.